2017
DOI: 10.1016/j.drugalcdep.2017.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Contingency Management interventions for non-prescribed drug use during treatment for opiate addiction: A systematic review and meta-analysis

Abstract: HighlightsContingency management (CM) reduces other drug use in opiate addiction treatment.Meta-analyses did not find evidence of effectiveness for non-prescribed opiate use.CM is effective for cocaine, tobacco, opiates + cocaine, tobacco, polysubstance use.Evidence is lacking for long-term effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 63 publications
3
29
1
Order By: Relevance
“…Contingency management (CM) is an approach that involves offering rewards contingent on engagement in substance use treatment and on evidence of abstinence. CM has now accumulated a robust evidence base in a variety of contexts, including smoking cessation, 26,27 heavy drinking 28 and drug misuse [29][30][31][32][33][34][35] and, in a fairly recent trial of a 12-week CM intervention, it was found to be clinically effective and cost-effective in reducing stimulant misuse in a cohort of patients with severe mental illness. 36 Furthermore, the National Institute for Health and Care Excellence (NICE) has recommended that it be adopted in the UK.…”
Section: Resultsmentioning
confidence: 99%
“…Contingency management (CM) is an approach that involves offering rewards contingent on engagement in substance use treatment and on evidence of abstinence. CM has now accumulated a robust evidence base in a variety of contexts, including smoking cessation, 26,27 heavy drinking 28 and drug misuse [29][30][31][32][33][34][35] and, in a fairly recent trial of a 12-week CM intervention, it was found to be clinically effective and cost-effective in reducing stimulant misuse in a cohort of patients with severe mental illness. 36 Furthermore, the National Institute for Health and Care Excellence (NICE) has recommended that it be adopted in the UK.…”
Section: Resultsmentioning
confidence: 99%
“…Behavioural interventions have proved effective for the treatment of other forms of addiction [7577]. There is growing evidence that reducing punishment—such as incarceration—and adopting positive reinforcement for people with substance use improves their access to services, their reintegration into society, and, ultimately, public safety [7880].…”
Section: Discussionmentioning
confidence: 99%
“…A switch from methadone to buprenorphine 121 is an alternative or complementary strategy. The finding that methadone exposure duration is unrelated to craving suggests a lingering relapse risk during methadone maintenance and emphasizes the significance of its integration with non-pharmacological interventions including contingency management 122 or mindfulness-based techniques 123 . A potentially beneficial effect of buprenorphine on opioid craving begs further validation.…”
Section: Discussionmentioning
confidence: 99%